NILAI-NILAI RELIGIUS DALAM KISAH NYATA “ADA YANG ABADI” KARYA EIDELWEIS ALMIRA DAN IMPLIKASI PADA PEMBELAJARAN BAHASA INDONESIA - Zebua, Seprianus (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
The background of this research is that there are still students with unstable conditions, so it is hoped that strong religious values ​​will be instilled so that they will be embedded and have an influence on students' daily lives. This type of research is descriptive qualitative research. The data source is writing or sentences in the true story There is an Immortal by Eidelweis Almira which contains religious values. The research results show that the true story "There is an Eternal" by Eidelweis Almira has religious values ​​regarding the value of truth, the value of beauty, the value of goodness or morals and religious values. Students are taught about life, taught to help each other, make sacrifices for their brothers and fellow humans, taught about cooperation, taught to accept the realities of life, taught about patience, surrender and asking for God's help. The suggestions put forward by researchers are (1) the results of the research can be used as a reference for teachers in teaching literature at school; (2) the research results can be used as a guide in understanding the religious values ​​contained in a true story; and (3) future researchers should be able to develop this research with a broader scope related to literary works.